Thinking About Behavior: Perspective on Meta-Behavior in Education - Amran, Muhammad Syawal; Zain, Suriana Mohd; Jamaludin, Khairul Azhar; Surat, Shahlan (Frontiers in Psychology, 2021)
Studies on metacognitive skills have started in the past 30 years and cover various fields, including education. In general, metacognitive skills refer to awareness and monitoring cognitive processes and their ability to sharpen the mind enhancement process. However, much attention has been given to metacognition alone and less focusing on its manifestation in behaviors. Thus, this study aims to conceptualize how metacognitive concepts can be adapted in the context of behaviors. In achieving this, an in-depth analysis of relevant behavioral theories and metacognitive models was conducted. The proposed conceptual framework, named the meta-behavior framework, underscores the importance of the thinking process before an individual engages in action. Undoubtfully, this skill is vital in influencing an individual to plan, monitor and evaluate his/her actions in daily life. In short, the proposed framework is essential in expanding the current knowledge terrain on psychology, which specifically provides a new perspective in understanding how the thinking process determines behavior.